Formation of ZnO nanorods via low temperature hydrothermal method for enzymatic glucose sensor - Nur Syafinaz Ridhuan; Khairunisak Abdul Razak; Zainovia Lockman (Penerbit Universiti Kebangsaan Malaysia, 2016)
In this study, zinc oxide (ZnO) nanorod arrays were synthesized using a simple hydrothermal reaction on a ZnO seeds/ITO substrate and applied for the fabrication of enzymatic glucose sensor. ZnO nanorod matrix provided a favourable environment for the immobilization of glucose oxidase (GOx) and introduced a shuttling way for electronic communication between GOx and electrode. The performance of different aspect ratio of ZnO nanorods that was produced by varying hydrothermal reaction time was studied. The aspect ratio of ZnO influenced the GOx enzyme immobilization. The morphology and structure of prepared ZnO nanorods were characterized by employing scanning electron microscopy (SEM), and X-ray powder diffraction (XRD). Electrochemical measurements of the sensor showed a reproducible sensitivity of 2.06 μA/cm2mM for ZnO matrix grown for 4 h with the aspect ratio of 8.0.